2016
DOI: 10.1177/0897190014568378
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Accuracy of Information Regarding Nonprescription Emergency Contraception

Abstract: Access to nonprescription EC in Rhode Island is very good. Sites not stocking EC should reassess plans for patients to obtain medication. There is need for reeducation on EC labeling to improve counseling provided over the telephone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Wilkinson's findings are similar to previous work by their group and others [2À10]. Findings from these mystery caller studies showed commonly that access was encouragingly high [1,3,5,7] but that pharmacy advice was not always accurate regarding product use or adverse effects [1,3,5,8,9]. Most importantly, many studies conducted after the 2014 legislative changes found misinformation was given about age restrictions [1,3,5,8À10].…”
supporting
confidence: 76%
“…Wilkinson's findings are similar to previous work by their group and others [2À10]. Findings from these mystery caller studies showed commonly that access was encouragingly high [1,3,5,7] but that pharmacy advice was not always accurate regarding product use or adverse effects [1,3,5,8,9]. Most importantly, many studies conducted after the 2014 legislative changes found misinformation was given about age restrictions [1,3,5,8À10].…”
supporting
confidence: 76%
“…Of 923 irrelevant, 12 were not in English . The 16 removed at later stage were not within the scope of the review, their topics being simulated patient encounters as part of pharmacist training; reviews or secondary analyses of SP studies presented elsewhere; phone or e‐mail rather than in‐person visits; full paper not available; or other reasons …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the availability of oral EC, international SPM studies [37][38][39]41,42,45] suggest that there are problems-especially with UPA. Some price differences-even between identical preparations-could also be identified, as in addition to international SPM studies on oral EC [11,12,[41][42][43][44][45][46][47]97,98], a national SPM study on a different indication has already identified significant price differences between CPs that are even located in the same city and in some cases only a few hundred metres apart [15].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other countries such as the USA [11,12,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], the study situation for Germany for the provision of self-medication consultations, availability and pricing is rather poor so far. In nationwide interviews of 25 CPs conducted at the end of 2015, i.e., after the OTC switch in March 2015, 96% of the respondents reported using a checklist for the provision of self-medication consultations for oral EC.…”
Section: Introductionmentioning
confidence: 99%